Visualizing the Landscape of Indo-Pacific Strategy Research in China (2013-2023) A CiteSpace-Based Analysis - Long, Liwei (Pacific International Journal, 2025)
This study conducted a systematic analysis of 531 articles on the “Indo-Pacific Strategy”, published in CSSCI and Peking University Core journals between 2013 and 2023, sourced from the China National Knowledge Infrastructure (CNKI) database. By employing CiteSpace visualization software and bibliometric methods, we constructed networks of author collaboration, institutional collaboration, and keyword co-occurrence. This approach revealed the developmental trajectory, research hotspots, and evolutionary trends within this field. The key findings indicate that: (1) Research interest in the “Indo-Pacific Strategy” has shown a consistent upward trend since 2018; (2) Primary research themes encompass the Belt and Road Initiative (BRI), India, the United States, China-U.S. relations, the Indo-Pacific region, and regional order; (3) High-frequency keywords such as “Trump (Administration)”, “U.S.-Japan Alliance”, and “India-U.S. relations” delineate the current research frontiers; (4) Research outputs are highly concentrated in 15 core journals; (5) A stable core research community has yet to emerge, as evidenced by the fragmented nature of the author collaboration network. Based on these findings, this paper proposes several future research directions, aiming to provide empirical data and theoretical references for further exploration in this field.